Effect of Magnesium and Copper Addition in Aluminum 1100 on Tensile Strength and Microstructure - Aldino Arifin, Fito; Junipitoyo, Bambang; Suprapto, Yuyun (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
In Indonesia there is abundant aluminum 1100 and aircraft structures also use aluminum because it has the advantage of light weight and good corrosion resistance, but aluminum 1100 itself has the disadvantage of being easily brittle. Testing will be carried out by melting aluminum 1100 and then adding several chemical elements, namely magnesium and copper. The addition of these elements can improve the mechanical properties of aluminum 1100. The final result of the tensile strength value in this study, the highest number is in specimen 12, namely with a variation in the composition of aluminum alloy (Al) 93.60%, copper (Cu) 4.9% and magnesium (Mg) 1.5% with a value of 75.96Mpa. While the results of the lowest tensile strength value obtained in specimen 1, namely with variations in the composition of aluminum alloy (Al) 94.90%, copper (Cu) 3.8% and magnesium (Mg) 1.2% with a value of 60.49Mpa. In specimen 7 to specimen 12, it increased by 14.28%.